SUPPLY CHAIN RISK MANAGEMENT IN THE FUTURE INDUSTRY IN INDONESIA IN FACING THE COVID-19 PANDEMIC - Oke Oktavianty; Rahmi Yuniarti; Ratih Ardia Sari; Endra Yuafanedi Arifianto (Center for Study and Journal Management FTI UMI, 2022)
The COVID-19 pandemic that has hit the world, especially Indonesia since March 2, 2020, has given rise to several impacts on the economy and worsened the export-import performance. Non-construction investment is at risk of slowing down due to the decline in prospects for exports of goods and services and disruption of production chains. This research was conducted on a furniture company in Pasuruan, East Java. The company obtains its raw materials from China at about 30% of its production needs with the main consumers come from United States. The initial stage of the research was to identify the business processes based on 4 core SCOR processes. The research method used was House of Risk (HOR) to identify the risk events and risk agents in HOR Phase I, and determine the preventive strategy on HOR Phase II. There were 45 risk events and 30 risk agents, where the risk agent with the highest ARP value was prioritized to obtain the risk management strategies. It was obtained social restrictions due to the COVID-19 pandemiccontribute the highest score of ARP values